Metabolic regulation of activins in healthy individuals and in obese patients undergoing bariatric surgery. Issue 5 (1st March 2020) - Perakakis, Nikolaos; Kokkinos, Alexander; Peradze, Natia; Tentolouris, Nikolaos; Ghaly, Wael; Tsilingiris, Dimitrios; Alexandrou, Andreas; Mantzoros, Christos S.
Abstract: Objective: Follistatin binds and inactivates activins, which are potent inhibitors of muscle growth and metabolism and are currently being developed for the treatment of obesity and type 2 diabetes (T2D). We have recently reported that follistatin is regulated by glucose (and not lipids) and can prospectively predict the metabolic improvements observed after bariatric surgery. We utilized novel assays herein to investigate whether activins are regulated by glucose or lipids, whether their circulating levels change after bariatric surgery and whether these changes are predictors of metabolic outcomes up to 12 months later. Design and Methods: Activin A, B, AB and their ratios to follistatin were measured in (a) healthy humans (n = 32) undergoing oral or intravenous lipid or glucose intake over 6 h, (b) morbidly obese individuals with or without type 2 diabetes undergoing three different types of bariatric surgery (gastric banding, Roux‐en‐Y bypass or sleeve gastrectomy) in two clinical studies (n = 14 for the first and n = 27 for the second study). Results: Glucose intake downregulates circulating activin A, B and AB, indicating the presence of a feedback loop. Activin A decreases (~30%), activin AB increases (~25%) and activin B does not change after bariatric surgery. The changes in activin AB and its ratio to follistatin 3 months after bariatric surgery can predict the BMI reduction and the improvement in insulin and HOMA‐IR observed 6 months postoperatively. Conclusion: Activins are implicated in glucose regulation in humans as part of a feedback loop with glucose or insulin and predict metabolic outcomes prospectively after bariatric surgery.